Cognitive Control Under Stress - Steinhauser, Marco; Maier, Martin; Hübner, Ronald (Psychological Science, 2007)
This study investigated the effect of stress on cognitive control in task shifting. Subjects shifted between two tasks in an explicit cuing paradigm. Shift costs (i.e., performance decrements on task shifts relative to task repetitions) were measured for a long and a short cue-stimulus interval (CSI). Stress was varied by administering low-stress and high-stress IQ scales to two groups of subjects. In the low-stress group, shift costs were reduced with an increased CSI, a result that typically indicates anticipatory and shift-specific task-set reconfiguration. In the high-stress group, however, shift costs were independent of the CSI. This result is consistent with the idea that stress induces a change in the reconfiguration strategy, possibly to adapt to depleted resources.